Comparative study of diurnal and nocturnal sap flow of Quercus ilex and Phillyrea latifolia in a Mediterranean holm oak forest in Prades (Catalonia, NE Spain) - Barbeta, Adrià; Ogaya, Romà; Penuelas, Josep (Trees, 2012)
Droughts are a cyclical disturbance in Mediterranean ecosystems and climate change models forecast an increase of their frequency and severity. Some experimental and observational studies have shown that cooccurring species may cope with drier conditions with different strategies and present different responses. Here, we investigate sap ﬂow response to drought in order to explain the observed differential growth and mortality of Quercus ilex and Phillyrea latifolia at Prades Holm oak forest (NE Spain). We measured sap ﬂow of these species and compared their diurnal, nocturnal and seasonal patterns and their relationship with environmental variables. Both species described qualitatively similar daily patterns, either during daylight or night. Sap ﬂow rates were signiﬁcantly higher in P. latifolia except in autumn and spring. P. latifolia was more sensitive to soil moisture. Nocturnal sap ﬂow was detected in both species with no signiﬁcant differences and hourly rates suffered a progressive increase from 3 a.m. to dawn in most sampled nights. Our results indicate a better adaptation of P. latifolia to this site as it can take better advantage of wet periods while maintaining higher sap ﬂow rates during dry periods. Along with previous ecophysiological studies at the same location it may be inferred that at its drier distributional limit Q. ilex would be at disadvantage with respect to other species like P. latifolia, as the latter would cope better with increasing xeric conditions already occurring and further predicted for Mediterranean ecosystems. Our results also show nocturnal sap ﬂow to be relevant in individual water losses in these two species as they can be up to 35–40 % of daily sap ﬂow. Further research on the underlying mechanisms of this nocturnal sap ﬂow is required since it may also enhance early morning CO2 ﬁxation or nutrient supply to leaves.
Keywords: á; Drought; ilex á sap flow; nocturnal sap flow; nocturnal sap flow á; phillyrea latifolia; phillyrea latifolia á quercus; Quercus ilex; sap flow

Impact of stand density on water status and leaf gas exchange in Quercus ilex - Moreno, Gerardo; Cubera, Elena (Forest Ecology and Management, 2008)
Tree thinning reduces tree-to-tree competition and likely contributes to the improvement of tree water status and productivity in water-limited systems. In this study, we examined the importance of competition for water among Quercus ilex trees in open woodlands by comparing the water consumption and physiological status of trees located along stand density gradients which ranged from 10% (low density; LD) to 100% (high density; HD) of canopy cover. The study was carried out at two sites which differed in mean annual rainfall (506 and 816 L m 2 ; Dsite and Wsite , respectively). Predawn and midday leaf water potential (cd and cm, respectively) and CO2 assimilation rate (A) were measured every two weeks from mid May to mid September, in eight trees located along a stand density gradient at each site. Sap ﬂow and soil moisture were measured only at Dsite . Sap ﬂow was continuously recorded by sap ﬂowmeters (constant heating method) installed in 12 trees along two stand density gradients. Soil moisture (U) was measured every 20 cm for the ﬁrst meter and then every 50 cm up to 250 cm. Measurements were conducted in 18 soil proﬁles, 6 located in HD and 12 in LD (six beneath and six out the canopy). At Wsite , differences among stand densities for c and A were very small and emerged only at the end of the dry season. At Dsite , c (both predawn and midday), A, U, and sap ﬂow density were signiﬁcantly higher in LD trees than in HD ones. At Dsite , some water remained unused in the soil at the end of the dry season beyond the canopy in the LD areas, and trees did not experienced such an acute water deﬁcit (cd > 1 MPa) as the HD trees did (cd < 3 MPa). Summer tree transpiration at the stand level (Estand) tended to saturate with the increase of canopy cover. Estand increases by 32% when canopy cover goes from 50% to 100%. Results conﬁrmed that the increase of tree-to-tree competition with stand density was much more signiﬁcant at dry sites. In these sites, tree thinning is recommended as a way to maintain tree functioning
Keywords: leaf water potential; open woodland; photosynthesis; sap flow; Soil moisture

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl23710.1093/jxb/erl237The following values have no corresponding Zotero field: accession-num: 17229759
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Water-use strategies in two co-occurring Mediterranean evergreen oaks: surviving the summer drought - David, T. S.; Henriques, M. O.; Kurz-Besson, C.; Nunes, J.; Valente, F.; Vaz, M.; Pereira, J. S.; Siegwolf, R.; Chaves, M. M.; Gazarini, L. C.; David, J. S. (Tree Physiology, 2007)
In the Mediterranean evergreen oak woodlands of southern Portugal, the main tree species are Quercus ilex ssp. rotundifolia Lam. (holm oak) and Quercus suber L. (cork oak). We studied a savannah-type woodland where these species coexist, with the aim of better understanding the mechanisms of tree adaptation to seasonal drought. In both species, seasonal variations in transpiration and predawn leaf water potential showed a maximum in spring followed by a decline through the rainless summer and a recovery with autumn rainfall. Although the observed decrease in predawn leaf water potential in summer indicates soil water depletion, trees maintained transpiration rates above 0.7 mm day−1 during the summer drought. By that time, more than 70% of the transpired water was being taken from groundwater sources. The daily fluctuations in soil water content suggest that some root uptake of groundwater was mediated through the upper soil layers by hydraulic lift. During the dry season, Q. ilex maintained higher predawn leaf water potentials, canopy conductances and transpiration rates than Q. suber. The higher water status of Q. ilex was likely associated with their deeper root systems compared with Q. suber. Whole-tree hydraulic conductance and minimum midday leaf water potential were lower in Q. ilex, indicating that Q. ilex was more tolerant to drought than Q. suber. Overall, Q. ilex seemed to have more effective drought avoidance and drought tolerance mechanisms than Q. suber.
10.1093/treephys/27.6.79310.1093/treephys/27.6.793
Keywords: canopy conductance; groundwater; Hydraulic conductance; leaf water potential; Quercus ilex; Quercus suber; sap flow

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances